EFEKTIVITAS PEMBIAYAAN BANTUAN OPERASIONAL SEKOLAH PADA MADRASAH TSANAWIYAH SWASTA SIRAJUL HUDA DI KABUPATEN PIDIE JAYA - Erianti, Murniati, AR, Niswanto (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
ABSTRACT: Financing is one of the factors that influence the improvement of the quality of education. The purpose of this study is to figure out the effectiveness of the of School Operational Assistance financing in 1) the relevance of BOS financing; 2) Continuity of BOS financing; 3) Monitoring of BOS financing; 4) support and resistance of BOS financing at Sirajul Huda private Islamic Junior High School of Pidie Jaya. This study used the descriptive method with a qualitative approach. Data collection were done through observation, interviews and documentation study. The subjects of the study were headmaster, committees, teachers and treasurer. The results showed that: 1) the BOS funding had already relevant to BOS technical instructions. It can be seen from the RKAM and RKM drafting; 2) the continuity of BOS Financing at Sirajul Huda Private Islamic Junior High School of Pidie Jaya has not been maximal. It can be seen from the distribution time of BOS funds that are not in accordance to rules and regulations; 3) The BOS funding Monitoring was already done well. It can be seen from supervision by the District Monitoring Team that has been worked optimally, and 4) the BOS financing supporting at Sirajul Huda private junior high school has not been optimal. It can be seen from the less available of human resources. However, the inhibiting factors of the BOS financing at Sirajul Huda islamic private junior high school is still there. It can be seen from the lack of financing and have no other funding sources.KEYWORDS: effectiveness, financing, and school operational assistance ABSTRAK: Pembiayaan merupakan salah satu faktor yang mempengaruhi peningkatan mutu pendidikan. Tujuan penelitian ini adalah untuk mendapatkan gambaran tentang efektivitas pembiayaan BOS dalam: 1) Relevansi pembiayaan BOS; 2) Kontinuitas pembiayaan BOS; 3) Pengawasan pembiayaan BOS; 4) Dukungan dan hambatan pembiayaan BOS pada MTsS Sirajul Huda di Kabupaten Pidie Jaya. Penelitian ini menggunakan metode deskriptif dengan pendekatan Kualitatif. Teknik pengumpulan data melalui; observasi, wawancara dan studi dokumentasi. Subjek penelitian adalah kepala madrasah, komite, guru dan bendahara. Hasil penelitian menunjukkan bahwa: 1) Pembiayaan BOS sudah relevan dengan petunjuk teknis BOS. Hal ini dapat dilihat dari tersusunnya RKAM dan RKM; 2) Kontinuitas Pembiayaan BOS yang ada selama ini belum maksimal. Hal ini dapat dilihat dari waktu penyaluran dana BOS tidak sesuai ketentuan; 3) Pengawasan pembiayaan BOS sudah berjalan dengan baik. Hal ini dapat dilihat dari pengawasan oleh Tim Pengawas Kabupaten yang berjalan dengan baik; dan 4) Pendukung pembiayaan BOS belum berjalan dengan maksimal. Hal ini dapat dilihat dari SDM yang masih kurang. Sedangkan faktor menghambat pembiayaan BOS masih ada. Hal ini dapat dilihat dari pembiayaan yang masih kurang, tidak memiliki sumber dana lainnya.KATA KUNCI: efektivitas, pembiayaan dan bantuan operasional sekolah